2003
DOI: 10.1007/s12144-003-1015-5
|View full text |Cite
|
Sign up to set email alerts
|

From attitudes to behaviour: Basic and applied research on the theory of planned behaviour

Abstract: The present article traces the development of the theory of planned behaviour, from early research on the attitude-behaviour relationship through the theory of reasoned action. In particular, it is argued that a perceived lack of correspondence between attitude and behaviour led to examination of variables that either moderated (e.g., attitude strength, measurement correspondence) or mediated (behavioura! intention) the relationship between attitudes and behaviour. Several meta-analytic reviews provide strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(142 citation statements)
references
References 24 publications
6
129
0
7
Order By: Relevance
“…Taken together, these findings suggest that effects of testosterone and cortisol manifest more strongly on the behavioral rather than on a cognitive/emotional level. This reinforces the notion that people's attitudes and actions are two different things (e.g., Ajzen & Fishbein, 1977;Armitage & Christian, 2003). Possibly, the link between endocrine factors and attitudes is weaker because it is more strongly influenced by intervening and moderating variables.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Taken together, these findings suggest that effects of testosterone and cortisol manifest more strongly on the behavioral rather than on a cognitive/emotional level. This reinforces the notion that people's attitudes and actions are two different things (e.g., Ajzen & Fishbein, 1977;Armitage & Christian, 2003). Possibly, the link between endocrine factors and attitudes is weaker because it is more strongly influenced by intervening and moderating variables.…”
Section: Discussionsupporting
confidence: 80%
“…Correlations between pro-environmental behaviors and attitudes are typically only moderate (Bamberg & Möser, 2007), which is in line with the well-known social psychological findings of inconsistent relationships between attitudes and related behaviors (e.g., Ajzen & Fishbein, 1977;Armitage & Christian, 2003). Notably, most of the studies described above reported endocrine influences on the extent of undesirable behavior such as violence, aggression, or dominance.…”
Section: Introductionsupporting
confidence: 82%
“…Beliefs about the presence of issues that may help or hinder performance of the behavior give rise to perceived behavioral control (7). Importantly, each aspect can be weighted, as behavioral intention is predicted to be influenced only by those aspects which are salient to the individual, and this may vary from person to person (8). Figure 1 provides an overview of the theory.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 illustrates how ELM variables are potentially antecedents of TPB variables, which in turn are the antecedents of behaviour change. (This paper concentrates on relationships between the two theories, not inter-relationships within the TPB, which are well documented elsewhere (Armitage and Christian, 2003;Armitage and Conner, 2001;Hardeman et al, 2002).) ELM and TPB variables are potential links in a chain from communication to behaviour.…”
Section: Ordering the Frameworkmentioning
confidence: 96%